Miroslav Volf's Theosophy and Charitable Social Living - Yulia Putri; Rahel Gloria Merlinda Suriani; Fetriani; Yohana Sefle; Alfonso Munte (Athena: Journal of Social, Culture and Society, 2023)
Worldviews of Christian practice across society globally inevitably revolve around Christianity's mainstream sense of patterned spirituality. Christian spirituality is such a diverse practice, though, that researchers have decided spirituality itself is unable to be quantified as one segmented behavior. Christian spirituality is neither merely a hierarchical ladder nor simply something designed to attain ultimate spirituality. Patterns of glorifying private Christian spirituality become the locality of Miroslav Volf's criticism as both philosopher and theologian. The data collected here represents qualitative research utilizing interview techniques recorded on smartphones. The recordings were processed into verbatim transcripts as a medium for gathering narratives related to the subjects' experiences. We conducted qualitative research through interview techniques, as Christian life and the practices of society and self are closely related to the subjects' lives and their social engagement. The results showed that spirituality is both a tension and a celebration of diversity within Christian practices in everyday life. Spirituality within the research context of the Christian youth congregation in Palangka Raya Church exists within responsibilities, appreciations, mutual learnings, and becoming immersed within social axioms as Christian citizens in and through life in all of its complexities